2020
DOI: 10.5603/cj.a2019.0087
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of CD68+ cells correlates positively with matrix metalloproteinase 2 expression in the arteries used as aortocoronary bypass grafts. Possible clinical implications

Abstract: Background: Late failure of arterial aortocoronary conduits may result from abnormal activity of cells found in the vessel wall, including macrophages. The purpose of this study was to assess if there are any associations between the number of macrophages and overexpression of matrix metalloproteinases (MMPs) in the wall of arterial grafts, as well as their clinical significance. Methods: This study involved 128 consecutive patients with a mean age of 64.9 ± 9.7 years who underwent elective surgery for coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The findings of this study should be treated as complementary one for the previous articles focused on degeneration of aorto-coronary grafts and published by the same research team [13,19,20]. There it was pointed that macrophages may play a crucial role in grafts disease eventually leading to their occlusions and clinically recurrence of CAD symptoms [13].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The findings of this study should be treated as complementary one for the previous articles focused on degeneration of aorto-coronary grafts and published by the same research team [13,19,20]. There it was pointed that macrophages may play a crucial role in grafts disease eventually leading to their occlusions and clinically recurrence of CAD symptoms [13].…”
Section: Discussionsupporting
confidence: 54%
“…More researchers stress a crucial role of macrophages in pathogenesis of aorto-coronary grafts failure [17,18]. It was previously found that distribution of macrophages, defined as CD68+ cells, differed between vessels with favorable and poor long-term outcomes [19]. The vascular segments with relatively high representation of macrophages in the inner vascular layers were found to be more prone to development of preterm graft disease related to early CAD symptoms recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the neurodegeneration observed in PD can be partially attributed to the dysregulation of cellular functions influenced by MMPs (Yanuck, 2019 ). For example, MMP1 and MMP13 increase the ability of human fibroblasts and dendritic cells to phagocytose, respectively (Perek et al, 2013 ; Rustenhoven et al, 2016 ; Hunter et al, 2018 ; Pelekanou et al, 2018 ; Yoon et al, 2020 ). In neurodegenerative disorders, microglial expression of MMP13 is upregulated in response to amyloid beta (Ito et al, 2007 ) and knockdown of MMP13 in APP/PS1E9 mice rescued learning and memory deficits (Zhu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%